Conceptualizing good global statehood: progressive foreign policy after the populist moment. Issue 1 (29th March 2023) - Gilmore, Jonathan
Abstract: This article explores the theoretical challenges for normatively progressive foreign policy following the rise of populist nationalism during the 2010s, using analytical concepts from the English School. It argues that populist nationalism exposes a problem of internal dissensus on the future trajectories of solidarist international society, within the Western states that have traditionally been its principal supporters. The 'populist moment' reveals problems of disconnection between domestic publics, the practices, and institutions of contemporary international society, and state actions that are premised in part on ethical regard for non-citizens. The article contends that, as an interface point between rooted communities and global ethical concerns, progressive foreign policy approaches have an important role to play in ameliorating these disconnections. However, these approaches must look beyond a simple 're-booting' of liberal internationalism, focussing instead on building a path towards solidarist international society that is rooted in everyday-lived experiences, communities, and identities within the state. Building upon theorizations of good international citizenship, the article advances an alternative framework of good global statehood, which draws upon a coproduction methodology as a means of creating progressive foreign policies that are better attuned to pluralism and diversity across, but also within state borders.